Stomatal Behavior of Cowpea Genotypes Grown Under Varying Moisture Levels - Munjonji, Lawrence; Ayisi, Kingsley K.; Boeckx, Pascal; Haesaert, Geert (Sustainability, 2017)
Drought is a major limitation to crop productivity worldwide. Plants lose most of their water through stomata, thus making stomata an important organ in the control of transpiration and photosynthesis. This study assessed the stomatal behavior of four cowpea genotypes grown under four moisture levels under hot semi-arid conditions. Stomatal conductance (gs) was measured at 47, 54, 70 and 77 days after planting (DAP). Biomass and carbon isotope composition ( 13C) were also determined at flowering. Genotype and moisture level significantly influenced gs. Genotypes varied in gs at vegetative stages (47 and 54 DAP) only. TVu4607 had higher gs under severe drought conditions at both 47 and 54 DAP. On the other hand, moisture level influenced gs at 54 and 70 DAP only. Stomatal conductance was severely restricted in cowpea under both moderate and severe drought conditions as gs was mostly below the threshold 0.10 mol m􀀀2 s􀀀1. Relationships between:biomass and gs, and 13C and gs were positive under severe drought only. The findings revealed that cowpea genotypes vary in gs under dry conditions and that the variation is more prominent at vegetative stage, suggesting that cowpea productivity in dry areas could be improved through selection of genotypes that maintain higher gs under dry conditions.
Article published in the Sustainability.; vol 10, 12 doi:10.3390/su10010012
Keywords: Carbon isotope composition; Cowpea; Stomatal conductance; Water stress; Drought; Food security -Climatic factors; Plants-Effect of drought on